O‘QUVCHILAR KONSTRUKTIV XULQ-ATVOR XUSUSIYATLARI SHAKLLANISHIDA NIZOLI VAZIYATLARGA MUNOSABAT USULLARI - Norqo‘ziyeva, D.Sh.; Mahammadova, R.S. (SCIENCE and SOCIETY, 2025)
The article examines the negative impact of interpersonal conflicts arising in the education system on the development of society, the factors of their occurrence, socio-psychological and medical aspects. Considerations for reducing the effectiveness of the education system are also presented.